PRMT1 Ablation in Endothelial Cells Causes Endothelial Dysfunction and Aggravates COPD Attributable to Dysregulated NF‐κB Signaling - Thi Thuy Vy Tran; Yideul Jeong; Suwoo Kim; Ji Eun Yeom; Jinwoo Lee; Wonhwa Lee; Gyu‐Un Bae; Jong‐Sun Kang (Advanced Science)
Abstract Endothelial dysfunction and senescence are pivotal in pulmonary diseases, including chronic obstructive pulmonary disease (COPD). Protein arginine methyltransferase 1 (PRMT1) is the major enzyme responsible for asymmetric arginine dimethylation and plays a role in diverse biological processes, including cardiovascular function. Yet, its role in endothelial cells (ECs) remains poorly understood. Here, the role of PRMT1 is investigated in ECs, particularly in the context of COPD pathogenesis. Endothelial‐specific PRMT1 knockout mice exhibit pulmonary hemorrhage, inflammation, barrier disruption, and apoptosis, accompanied by hyperactivation of nuclear factor kappa B (NF‐κB). Bulk RNA sequencing of whole lungs and single‐cell RNA sequencing of pulmonary ECs reveal that endothelial PRMT1 ablation results in a major alteration in inflammation‐related gene expression. In a COPD model, PRMT1 deficiency aggravates the COPD phenotypes, including enlarged alveolar spaces, increased cell death, and senescence. PRMT1 inhibition in ECs exacerbates tumor necrosis factor alpha‐triggered EC senescence and dysfunction attributable to NF‐κB hyperactivation. PRMT1 as a critical regulator of pulmonary EC function, preventing NF‐κB‐driven endothelial dysfunction and senescence is highlighted here.